PORTABLE AVIATION NAVIGATION CALIBRATION SYSTEM BASED ON RASPBERRY PI, HACK RF ONE, AND SOFTWARE DEFINED RADIO COMMUNICATION SYSTEM - ade irfansyah; Mohamad Rifai; Yuyun Suprapto; Meita Maharani; Bambang Bagus Harianto (Jurnal Penelitian)
Calibration procedures for the aviation navigation system which involve full size aircraft and its crew may be considered risky and high cost . This paper introduces the state of the art communication system to provide lower cost and flexible solutions based on Raspberry Pi, and SDR device Hack RF One, equipped with proper and aviation-related sensors, which later may be treated as unmanned aerial vehicle payload to replace flying aircraft aviation instruments. Design principles which mainly consist of both flexible communication and operating feasibility are explained in early of this paper. As a preliminary method, simple FSK modulation coupled with data integrity mechanisms are implemented to realize reliable but fast sensor data transmission. Data communication rate under a single board computer environment may achieve 40 kbps. Proposed system achieved a data transmission success rate as high as 88% in reasonable condition. In addition, the discussion of further system development is presented.